Carbon dot compound for memristor and preparation method thereof
By physically blending boron-doped carbon dots with triazine-based conjugated porous polymers, a carbon dot composite functional layer material suitable for artificial synapses was prepared, which solved the lack of simulated carbon dot memristors in the prior art. The problem of this method achieves low energy consumption and high stability of analog resistance change behavior.
Patent Information
- Application Number
- CN202411411535.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-18
AI Technical Summary
There is a lack of simulated carbon dot memristors suitable for artificial synapses in the prior art, which is difficult to meet the demand for high-performance memristors of neuromorphic computing devices.
By physically blending boron doped carbon dots (BCQDs) with triazine-based conjugated porous polymer (CPP), carbon dot composites with ultra-thin layered morphology of 1 to 2 nm are prepared as functional layer materials for use in Preparation of artificial synaptic memristors.
It realizes low-energy consumption and high-stability simulated resistance-change behavior, which is suitable for artificial synaptic field, and meets the demand for high-performance memristors in neuromorphic computing.
Smart Images

Figure CN119486576A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of storage computing materials and devices, and relates to a carbon dot composite for preparing an artificial synaptic memristor, and in particular to a carbon dot composite for preparing an analog memristor. Background Art
[0002] In the current era of big data and artificial intelligence, the explosive growth of data is driving the rapid development of new storage and computing devices. With the time memory effect, memristors are expected to be used as large-scale neural processors to achieve storage and computing integration of on-chip networks in an event-driven manner, breaking the von Neumann bottleneck and continuing Moore's Law, breaking through the current hardware limitations on computing power and storage capabilities.
[0003] According to the resistance change characteristics of memristors, memristors can be divided into two types: digital and analog. The former exhibits a sudden change in resistance and is suitable for information storage, while the latter exhibits a slow change in resistance and is suitable for artificial synapses. Memristors are usually composed of a bottom electrode, a functional layer, and a top electrode, among which the material of the functional layer is the key to determining the performance of the memristor.
[0004] In recent years, carbon dot-based memristors have gradually gained attention in new storage and computing devices. Carbon dots can be used as functional layer materials for memristors due to their advantages such as solution processability, wide range of raw material sources and biocompatibility, providing low cost, low power consumption and portability for memristors. Studies have found that carbon dots can regulate the performance of memristors through local electric field enhancement, electron capture and decapture, and light-sensing effects (Pei Yifei, et al. Nanoscale ,2020, 12: 13531-13539.; Zeng Tao, et al. Nanoscale Advances , 2021, 3: 2623-2631.;Hao Haotian, et al. Advanced Electronic Materials , 2023, 9: 2201195).
[0005] Carbon dot memristors usually exhibit digital characteristics, achieving abrupt switching between "ON" and "OFF" states under different bias voltages, which can be triggered by the formation and disconnection of conductive filaments, corresponding to the writing or erasing operations of information storage. For example, Ai Lin, et al. Advanced Science , 2023, 10: 2207688) and Li et al. Materials Chemistry Frontiers , 2022, 6: 1098-1106) developed carbon dot memristors that exhibit bipolar resistive switching behavior; in addition, Hao et al. (Hao Haotian, et al. Small Methods, 2024:2301454) A boron-doped carbon dot was prepared using pyrene and boric acid as raw material and dopant, respectively. The corresponding memristor exhibited multi-order resistive switching behavior, and based on this, three-valued logic display and logic gate applications were also realized.
[0006] However, in the field of artificial synapses, analog memristors outperform digital memristors (Hu Hongrong, et al. Advanced Functional Materials , 2024, 34(20): 2302290.; Garbin Daniele, et al. IEEE Transactions on Electron Devices , 2015, 62(8): 2494-2501). Given the lack of analog carbon dot memristors in the current artificial synapse field, the development of such memristors is crucial to promote the development of brain-like neural hardware systems.
[0007] Based on the composite modification strategy of carbon dot materials with organic polymers, it is expected to promote the research and development of analog carbon dot memristors by precisely controlling the conductive channels of the device. This is of great significance for building a carbon-based interactive artificial intelligence system that can efficiently process complex environmental information. In view of this, it is particularly necessary and important to develop a carbon dot composite designed for artificial synaptic memristors to meet the urgent needs of neuromorphic computing devices. Summary of the invention
[0008] The purpose of the present invention is to provide a carbon dot composite, which is used as a functional layer material in an artificial synaptic memristor, aiming to achieve low-energy and highly stable analog resistive switching behavior and meet the needs of neuromorphic computing for high-performance memristors.
[0009] The carbon dot composite of the present invention is a composite with an ultra-thin layered morphology of 1 to 2 nm obtained by physically blending boron-doped carbon dots BCQDs and triazine-based conjugated porous polymers to fully attach the boron-doped carbon dots to the triazine-based conjugated porous polymers.
[0010] Furthermore, the present invention preferably uses boron-doped carbon dots and triazine-based conjugated porous polymer in a raw material mass ratio of 5:(0.2-0.4) for preparing the carbon dot composite.
[0011] Specifically, the boron-doped carbon dots are obtained by solvothermal reaction in an N,N-dimethylformamide solvent system using 1,3,6-trinitropyrene and boric acid as raw materials.
[0012] Furthermore, the solvothermal reaction is preferably carried out at 190-200°C.
[0013] More specifically, the boron-doped carbon dots described in the present invention are referenced to (Hao Haotian, et al. Small Methods , 2024: 2301454).
[0014] Specifically, the triazine-based conjugated porous polymer is a polymer composed of 2,4,6-triphenyl-1,3,5-triazine connected to 9,9-dialkylfluorene with different alkyl chains as repeating units, and the molecular weight of the polymer ranges from 25 to 30 kDA.
[0015] Furthermore, the number of carbon atoms in the alkyl chain of the 9,9-dialkylfluorene is 2 to 16.
[0016] More specifically, the triazine-based conjugated porous polymer of the present invention is preferably a polymer CPP composed of 2,4,6-triphenyl-1,3,5-triazine connected with 9,9-dihexylfluorene as repeating units.
[0017] The carbon dot composite of the present invention has the property of being processable in solution, and can be used as a memristor functional layer material for the preparation of an artificial synaptic memristor.
[0018] Furthermore, the present invention also provides a method for preparing the carbon dot composite, which specifically comprises:
[0019] 1) Selecting a triazine-based conjugated porous polymer as a base material, adding chlorobenzene to obtain a corresponding suspension, using an ultrasonic crusher to sonicate the suspension, and filtering to obtain a triazine-based conjugated porous polymer chlorobenzene dispersion that can be uniformly dispersed in chlorobenzene;
[0020] 2) drying to remove chlorobenzene in the triazine-based conjugated porous polymer chlorobenzene dispersion, and then adding chloroform to obtain a triazine-based conjugated porous polymer chloroform dispersion with better dispersibility;
[0021] 3) Boron-doped carbon dots prepared by 1,3,6-trinitropyrene and boric acid solvothermal method were used as raw materials for constructing carbon dot composites, and added into triazine-based conjugated porous polymer chloroform dispersion for ultrasonic blending to prepare carbon dot composite chloroform dispersion.
[0022] Furthermore, the present invention also provides an artificial synaptic memristor prepared using the carbon dot composite of the present invention as a functional layer material, wherein the carbon dot composite chloroform dispersion prepared above is prepared on a bottom electrode by spin coating to obtain a composite functional layer, and then a top electrode is evaporated using a mask to prepare a corresponding carbon dot composite-based memristor device.
[0023] The carbon dot composite-based memristor of the present invention is composed of a top electrode, a composite functional layer and a bottom electrode from top to bottom, wherein the top electrode material can be aluminum, silver or gold, the intermediate composite functional layer material is composed of the carbon dot composite described in the present invention, and the bottom electrode material can be composed of indium tin oxide, silicon or tin fluoride.
[0024] The carbon dot composite-based memristor prepared by the present invention can exhibit low power consumption (32.56 nJ) and continuous slow-changing resistance behavior, and is suitable for the field of artificial synapses and for the preparation of analog memristors. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a synthetic route and structural schematic diagram of triazine-based conjugated porous polymer CPP.
[0026] Figure 2 This is the Fourier infrared spectrum of triazine-based conjugated porous polymer CPP.
[0027] Figure 3 This is a transmission electron microscope image of the carbon dot composite BCQDs@CPP.
[0028] Figure 4 This is an atomic force microscope image of the carbon dot composite BCQDs@CPP film.
[0029] Figure 5 It is a layered morphology image of a carbon dot composite-based memristor.
[0030] Figure 6 is the cyclic current-voltage curve of the carbon dot composite-based memristor.
[0031] Figure 7 It is a relevant representation of the artificial synaptic plasticity exhibited by carbon dot composite-based memristors.
[0032] Figure 8 It is a carbon dot composite-based memristor used to simulate the learning and forgetting process of the human brain. Implementation
[0033] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0034] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0035] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0036] The boron-doped carbon dots BCQDs used in the embodiments of the present invention refer to the literature (Hao Haotian, et al. Small Methods , 2024: 2301454) was prepared by the method: 1,3,6-Trinitropyrene (400 mg, 1.19 mmol) and boric acid (2.8 g, 8.33 mmol) were weighed into a reactor filled with N,N-dimethylformamide (30 mL), and ultrasonic treatment was performed to uniformly disperse the raw materials in the solution; the reactor was sealed and placed in an oven for hydrothermal reaction at 195°C for 24 h.
[0037] After the reactor was cooled to room temperature, the reaction solution was filtered once with a filter head with a pore size of 0.22 μm, and then the filtrate was placed in a dialysis bag and dialyzed three times in deionized water (12 h each time) to remove excess DMF and small molecule impurities; then the mixture in the dialysis bag was filtered with filter paper, and the obtained precipitate was freeze-dried to prepare the product BCQDs. Example
[0038] Example 1
[0039] Figure 1 The following is a synthetic route and structural characteristic diagram of triazine-based conjugated porous polymer CPP. The specific synthetic method is:
[0040] Weigh 2,7-dibromofluorene (1 g, 3.1 mmol) and tetrabutylammonium chloride (111 mg, 0.4 mmol) into a 100 mL reaction bottle, evacuate and fill with nitrogen, repeat three times to ensure that the reaction bottle is filled with an inert atmosphere. Inject dimethyl sulfoxide (5 mL) and 50% sodium hydroxide aqueous solution (5 mL) into the reaction bottle under nitrogen atmosphere, stir for 30 min, then add bromohexane (1.3 g, 8 mmol), and react at room temperature for 12 h.
[0041] The reaction solution was extracted with dichloromethane and a large amount of deionized water. The organic phase was collected and purified by silica gel column chromatography after the solvent was removed to obtain a white product C1 (1.18 g, 86%).
[0042] 1 H NMR (400MHz, Chloroform-d) δ (ppm): 7.52 (d, J= 8.0Hz, 2H), 7.45 (dd, J= 7.8, 1.6Hz, 4H), 1.94-1.88 (m, 4H), 1.14-1.02 (m, 12H), 0.78 (td, J=7.2, 1.4Hz, 6H), 0.57 (dd, J= 10.3, 5.9Hz, 4H).
[0043] C1 (985 mg, 2 mmol) was added to a 50 mL Schlenk bottle. The evacuation and nitrogen filling were repeated three times to ensure that the reaction bottle was filled with an inert atmosphere. Redistilled tetrahydrofuran solvent (25 mL) was added under nitrogen protection. n-Butyl lithium (2.5 M, 2.4 mL, 6 mmol) was added dropwise at -78 °C. The reaction was stirred for 1 h. Isopropyl pinacol borate (1.96 mL, 9.6 mmol) was then added. The reaction system was gradually warmed to room temperature and the reaction was allowed to proceed overnight.
[0044] After the reaction was completed, saturated brine and dichloromethane were added for extraction, and the solvent was removed by a vacuum rotary evaporator. The crude product was purified by silica gel column chromatography to obtain a white powder product C2 (540 mg, 46%).
[0045] 1 H NMR (400MHz, Chloroform-d) δ (ppm): 7.83 (d, J= 7.6Hz, 2H), 7.77(s, 2H), 7.74 (d, J= 7.6Hz, 2H), 2.06-1.98 (m, 4H), 1.41 (s, 24H), 1.13-0.99 (m, 12H), 0.76 (t, J= 7.1Hz, 6H), 0.61-0.52 (m, 4H).
[0046] C2 (88 mg, 0.15 mmol), 2,4,6-tris(4-bromophenyl)-1,3,5-triazine (55 mg, 0.1 mmol), tetrakis(triphenylphosphine)palladium (8 mg, 0.007 mmol) and potassium carbonate (69 mg, 0.5 mmol) were added to a double-necked reaction bottle, and the vacuum was evacuated and filled with nitrogen. This process was repeated three times to ensure that the reaction bottle was filled with an inert atmosphere. Deionized water (5 mL) and redistilled tetrahydrofuran (20 mL) were injected under nitrogen protection, the temperature was raised to reflux of the solvent, and the reaction was allowed to proceed overnight.
[0047] After the reaction was completed and cooled to room temperature, the reaction solvent was filtered out, and the filter cake was washed with deionized water, anhydrous ethanol and tetrahydrofuran in sequence and dried to obtain a light yellow triazine-based conjugated porous polymer CPP (97 mg).
[0048] The triphenyltriazine group is the key repeating unit of CPP, which is connected by alkylfluorene groups. Figure 2 In the infrared spectrum, 2800-3000cm -1 (Region I) The absorption peak indicates the presence of CH stretching vibration on the alkyl chain of CPP; 1300-1650cm -1(Region II) The absorption peaks indicate the presence of triazine groups in CPP; 1175 and 1013 cm -1 (Region III) The signal is attributed to the CH out-of-plane bending vibration absorption peak; 814 cm -1 (Region IV) The signal peak belongs to the CH in-plane bending vibration absorption peak.
[0049] Example 2
[0050] 50 mg of triazine-based conjugated porous polymer CPP was weighed and added into 30 mL of chlorobenzene to obtain a suspension, which was then sonicated for 6 h using an ultrasonic crusher equipped with a 12 mm probe (500 W). During this period, the beaker containing the suspension was cooled using ice cubes several times.
[0051] The suspension after ultrasonic treatment was stirred in a 50°C water bath for 24 h, filtered with filter paper, and then filtered with a filter element with a pore size of 0.22 μm to obtain a uniformly dispersed CPP chlorobenzene dispersion.
[0052] Take 200 μL of the above CPP chlorobenzene dispersion and place it in a 60°C oven, dry it for 5 hours to remove chlorobenzene, and immediately add 1 mL of chloroform solvent to obtain a uniformly dispersed CPP chloroform dispersion with a concentration of 0.3 mg / mL, which is used to prepare a composite functional layer film with good film-forming quality.
[0053] 5 mg of BCQDs were weighed and placed in 1 mL of CPP chloroform dispersion and ultrasonically treated for 1 h to allow BCQDs to fully adhere to CPP to obtain a uniformly dispersed BCQDs@CPP composite chloroform dispersion.
[0054] Figure 3 The transmission electron microscopy image (a) and the local high-resolution transmission electron microscopy image (b) of the BCQDs@CPP composite are provided. It can be seen from the figure that the particle size of BCQDs is about 3nm, and the average lattice spacing is about 0.213nm, corresponding to the (100) crystal plane of graphite, indicating that the synthesized BCQDs have a graphite-like structure, which is consistent with the literature (Hao Haotian, et al. Small Methods , 2024: 2301454), which is consistent with the results reported by the journal, proving that the morphology and structure of the prepared BCQDs are correct and have been successfully composited on CPP.
[0055] Example 3
[0056] The chloroform dispersion of BCQDs@CPP complex (60 μL) was spin-coated on an indium tin oxide (ITO) glass substrate at a speed of 1500 rpm and a time of 40 s by spin coating, and then annealed on a hot stage at 80 °C for 30 min to prepare the composite functional layer of the artificial synaptic memristor.
[0057] Figure 4The atomic force microscope image of the composite film is given, and its surface root mean square roughness value is 0.078nm. The straight line marked in the figure just crosses four layers of film. From the corresponding contour line diagram, it can be seen that the functional layer is mainly composed of layered composites, and the thickness of each layer is between 1 and 2nm.
[0058] Furthermore, using a circular hole mask with a diameter of 100 μm, a layer of aluminum (Al) top electrode with a thickness of 70 nm and a diameter of 100 μm was evaporated on the composite functional layer by thermal evaporation (evaporation rate of 3 Å) to obtain a carbon dot composite-based memristor.
[0059] The structure of the carbon dot composite-based memristor is represented as Al / BCQDs@CPP / ITO, as shown in Figure 5 As shown in (a), it has a layered morphology, which includes a glass substrate, an ITO bottom electrode (100 nm), a composite functional layer (110 nm), and an Al top electrode (70 nm) from bottom to top. Figure 5 Middle (b) is a scanning electron microscope image of the cross-section of the memristor device, where the yellow is the ITO bottom electrode, the blue is the composite functional layer, and the purple is the Al top electrode.
[0060] Application Example 1
[0061] The carbon dot composite-based memristor prepared in Example 3 was used to irradiate the device from the bottom with an ultraviolet light source for 20 minutes, and then a FS-Pro semiconductor parameter tester was used to measure the cyclic current-voltage curve for 50 times.
[0062] Figure 6 The observation results show that IV The (current-voltage) curve shows high repeatability in 50 cycles and exhibits a continuous and slow-changing analog characteristic, which is significantly different from the digital characteristics presented by most carbon dot memristors, thus opening up the unique performance and application prospects of carbon dot materials in the field of analog carbon dot memristors.
[0063] Application Example 2
[0064] An electric pulse (4V, 50μs) was applied to the carbon dot composite-based memristor after UV irradiation. It was found that a single stimulus could induce a current response phenomenon, and the current gradually decayed after the pulse voltage was removed. The device showed the characteristics of excitatory postsynaptic current (EPSC) in biological synapses ( Figure 7 Based on the current response, the power consumption is calculated to be as low as 32.56nJ, which is helpful for the development of brain-like neural applications.
[0065] Figure 7In figure b, a pair of pulses (4V, 50μs) with an interval of 50μs is applied to the device. The maximum value of the second EPSC caused by electrical stimulation is greater than the maximum value of the first EPSC. The device exhibits the double-pulse facilitation phenomenon in biological synapses.
[0066] Figure 7 In the figure, electrical stimulation pulses of different amplitudes (2.0, 2.5, 3.0, 3.5 and 4.0 V) were then applied to the carbon dot composite-based memristor device. The memory retention of the device increased with the increase of the amplitude, showing stimulation amplitude-dependent plasticity.
[0067] Figure 7 In middle d, the applied pulse frequency was increased from 3.33kHz to 10.0kHz, and the memory retention of the device also increased accordingly, showing stimulation frequency-dependent plasticity.
[0068] Application Example 3
[0069] The carbon dot composite-based memristor prepared in Example 3 was used to simulate the artificial synaptic "learning-forgetting-relearning-reforgetting" process.
[0070] Figure 8 Figure a shows the learning process of the artificial synapse. By continuously applying 20 pulses (4V, 50μs) with an interval of 50μs to the device, the current value representing the memory strength gradually increases, which is similar to the short-term memory of the human brain.
[0071] After the stimulation signal was removed, it was found that the final memory strength remained at the initial maximum memory strength (denoted as I max ) is about 15% ( Figure 8 (b)
[0072] Then, the synaptic device was made to perform learning operations again, and it was found that the memory strength finally reached I max 120% of Figure 8 (c) significantly increases the upper limit of the device's memory strength. The reason may be that when training again, the conductive filaments remaining in the device after the previous training make the device easier to conduct, showing a more obvious memory strength in the same learning process.
[0073] Figure 8 Middle d shows that after the stimulus signal is removed again, the final memory strength remains at I max The memory strength is about 42% higher than that in the first forgetting process, showing long-term memory ability.
[0074] Through the above-mentioned simulation of the memory process of "learning-forgetting-relearning-forgetting again", it can be seen that the carbon dot composite-based memristor prepared by the present invention, as an artificial synapse, has a learning and memory process similar to that of the human brain, and a stronger memory level can be obtained when learning again after forgetting information.
[0075] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A carbon dot composite, which is obtained by physically blending boron-doped carbon dots and triazine-based conjugated porous polymers, wherein the boron-doped carbon dots are fully attached to the triazine-based conjugated porous polymer to obtain a composite having an ultra-thin layered morphology of 1 to 2 nm; The boron-doped carbon dots are obtained by solvothermal reaction of 1,3,6-trinitropyrene and boric acid in an N,N-dimethylformamide solvent system. The triazine-based conjugated porous polymer is a polymer composed of 2,4,6-triphenyl-1,3,5-triazine connected to 9,9-dialkylfluorene with different alkyl chains as repeating units.
2. The carbon dot composite according to claim 1, characterized in that The mass ratio of the boron-doped carbon dots to the triazine-based conjugated porous polymer is 5:(0.2-0.4).
3. The carbon dot composite according to claim 1, characterized in that The alkyl chain in the 9,9-dialkylfluorene has 2 to 16 carbon atoms.
4. The carbon dot composite according to claim 3, characterized in that The 9,9-dialkylfluorene is 9,9-dihexylfluorene.
5. The carbon dot composite according to claim 1, characterized in that The solvent thermal reaction temperature is 190-200°C.
6. The method for preparing the carbon dot composite according to claim 1, comprising: 1) Selecting a triazine-based conjugated porous polymer as a base material, adding chlorobenzene to obtain a corresponding suspension, using an ultrasonic crusher to sonicate the suspension, and filtering to obtain a triazine-based conjugated porous polymer chlorobenzene dispersion that can be uniformly dispersed in chlorobenzene; 2) drying to remove chlorobenzene in the triazine-based conjugated porous polymer chlorobenzene dispersion, and then adding chloroform to obtain a triazine-based conjugated porous polymer chloroform dispersion with better dispersibility; 3) Boron-doped carbon dots prepared by 1,3,6-trinitropyrene and boric acid solvothermal method were used as raw materials for constructing carbon dot composites, and added into triazine-based conjugated porous polymer chloroform dispersion for ultrasonic blending to prepare carbon dot composite chloroform dispersion.
7. Use of the carbon dot composite according to claim 1 in preparing an artificial synaptic memristor.
8. The use according to claim 7, characterized in that The artificial synaptic memristor is an analog memristor.
9. An artificial synaptic memristor, which is composed of a top electrode, a composite functional layer and a bottom electrode from top to bottom, wherein the composite functional layer is formed by spin coating a chloroform dispersion of the carbon dot composite according to claim 1 on the bottom electrode.